DO THE BIG FIVE PERSONALITY FACTORS AFFECT KNOWLEDGE SHARING BEHAVIOUR? A STUDY OF MALAYSIAN UNIVERISTIES - Pei-Lee, Teh; Chen, Chen Yong; Chin, Wei Chong; Siew, Yong Yew (Malaysian Journal of Library and Information Science, 2017)
This study aims to develop an integrative understanding of the Big Five Personality (BFP) factors supporting or inhibiting individuals’ online entertainment knowledge sharing behaviours. Survey data are collected from 255 university students from two Malaysian universities. As hypothesised, structural equation modelling shows that extraversion and neuroticism are positively related to the attitude towards knowledge sharing. Openness to experience is found to have an inverse relationship with the attitude towards knowledge sharing. Subjective norm is positively related to the attitude towards knowledge sharing. Both attitude towards knowledge sharing and subjective norm are found to be independently and significantly related to the intention to share knowledge, which significantly influences the knowledge sharing behaviour. The research model proposed in the present study is useful to other researchers seeking to understand the personality factors that influence the knowledge sharing behaviour among the organisational communities. The results of this study provide empirical evidence for a new model that shows that the BFP factors are implicated in individuals’ knowledge sharing behaviour. This study and its findings have filled the research gap in the literature of the BFP factors and knowledge sharing behaviours. Furthermore, the inclusion of the BFP factors in the Theory of Reasoned Action framework is an important distinction that other studies have not established.